Other Worlds Here : Honoring Native Women's Writing in Contemporary Anarchist Movements - Warburton, Theresa (Book collections on Project MUSE., 2021)
"This book examines the interaction of literature and radical social movement, exploring how to address the limitations of contemporary anarchist politics through attentive engagement with Native women's literatures"--